2012
DOI: 10.1021/cs300395a
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study of Furfural Conversion to Furan, Furfuryl Alcohol, and 2-Methylfuran on Pd(111)

Abstract: Dispersion-corrected density functional theory calculations were performed to investigate the adsorption of furan, furfural, furfuryl alcohol, and 2-methylfuran as well as the reaction barriers for their interconversion. The most stable configuration for furan, furfural, furfuryl alcohol, and 2methylfuran entails the furan ring lying flat on the surface, centered over a hollow site. We performed an elementary step analysis for the reaction of furfural to furan, furfuryl alcohol, and 2-methylfuran. Thermodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
225
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(252 citation statements)
references
References 44 publications
25
225
2
Order By: Relevance
“…The aromatic ring is centered at the three-fold fcc site [45] so that conjugated C=C bonds can bind to either the bridge site or to the Pd top site. On Pd(111), similar furfural adsorption geometries have been recently reported by Vorontnikov et al using the PBE-D3 functional [27]. We further observe that, although the adsorption geometries do not change significantly due to dispersion effects, the binding energies, defined as BE = E ads* − E * − E ads(g) ( Table 2), are strongly affected.…”
Section: Furfural and Furfuryl Alcohol Adsorptionsupporting
confidence: 88%
See 1 more Smart Citation
“…The aromatic ring is centered at the three-fold fcc site [45] so that conjugated C=C bonds can bind to either the bridge site or to the Pd top site. On Pd(111), similar furfural adsorption geometries have been recently reported by Vorontnikov et al using the PBE-D3 functional [27]. We further observe that, although the adsorption geometries do not change significantly due to dispersion effects, the binding energies, defined as BE = E ads* − E * − E ads(g) ( Table 2), are strongly affected.…”
Section: Furfural and Furfuryl Alcohol Adsorptionsupporting
confidence: 88%
“…Using DFT calculations and semiempirical corrections based on a QM/MM approach, Tonigold et al were able to determine adsorption energies of benzene and pyridine in good agreement with experiments on Au(111) [26]. Calculations using the PBE-D3 method of dispersion correction have also been extended recently to mechanistic studies of furfural conversion on Pd [27]. In spite of these advances, however, trends-based analyses that focus on how dispersion forces impact the thermochemistry and kinetics of surface reactions are still relatively rare, and this contribution seeks to provide such trends for the specific case of furfural hydrogenation.…”
Section: Introductionmentioning
confidence: 95%
“…In contrast, there is a strong band hybridization between furfural and Pt(111) in the flat configuration due to the direct C−Pt bonds. The tilt configuration on Cu(111) versus flat on Pd(111) has been used to explain 49 the high selectivity toward hydrogenation on Cu(111) because the channel for the activation of CC is effectively closed. Similarly here, enhanced selectivity for furfural hydrogenation with PtSn intermetallic NPs should be also due to its preferred tilted configuration on PtSn(110) and (100).…”
Section: Resultsmentioning
confidence: 99%
“…Supporting this notion, singlecrystal studies of benzyl alcohol and benzaldehyde (functionally similar to furfural) on Pd(111) have shown that DC to produce benzene is dominant when the molecules can adopt a flat-lying conformation 22 . In addition, density functional theory calculations show that the furan ring in furfural preferentially adsorbs in a threefold hollow site for flat-lying structures 7,8,23 . Thus, we expect that DC and RH occur primarily on threefold terrace sites where a large contiguous ensemble of sites is available.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, reaction steps such as aldehyde hydrogenation (AH) and hydrodeoxygenation (HDO) necessary for conversion of furfuryl oxygenates to desirable fuels (furfuryl alcohol and methylfuran) do not occur as readily. [3][4][5][6][7][8] Figure 1 depicts the major reaction pathways for furfural hydrogenation.…”
mentioning
confidence: 99%